2022
DOI: 10.1101/2022.09.01.506267
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Roots fuel cell produces and stores clean energy

Abstract: In recent years, extensive scientific efforts are conducted to develop clean bio-energy technologies that have the potential to compete with the contaminating fossil fuels. Electricity production was previously generated from photosynthetic organisms in bio-photo electrochemical cells (BPECs), and microbial fuel cells (MFCs). The main approach of such methods was to exploit the ability of the organisms to perform external electron transfer (EET) to reduce the anode of an electrochemical cell. By far, these met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Previous studies have reported the utilization of the protein Cytochrome C (Cyt) as an indicator for the presence of reducing molecules in a solution [31]. The absorption spectrum of fully oxidized Cyt shows a single peak at λ=475 – 600 nm with a maximum at 530 nm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported the utilization of the protein Cytochrome C (Cyt) as an indicator for the presence of reducing molecules in a solution [31]. The absorption spectrum of fully oxidized Cyt shows a single peak at λ=475 – 600 nm with a maximum at 530 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Absorption of LB fully oxidized Cyt and a mixture of Cyt +LB after 30 incubation. The intensity increase at 550 nm indicates Cyt reduction [31] Absorption spectra of LB (black), Cyt (red), and Cyt + LB (blue). b Average absorption at 550 nm of LB (black), Cyt (red), and Cyt + LB (blue).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent works have reported the release of the redox active molecules Nicotinamide adenine dinucleotide (NADH) and Nicotinamide adenine dinucleotide phosphate (NADPH) from various organisms such as cyanobacteria 25,30 , microalgae 26 , seaweeds 32 , plant’s leaves 29,34,36 , roots 38 and sea anemones 39 . These molecules can apply as electron mediators in bio-electrochemical cells catalysing electrons transport between the respiration and photosynthetic pathways of the cells and the external anode.…”
Section: Resultsmentioning
confidence: 99%
“…The photocurrent production from seaweeds and plants is about 1000 times greater than reported for micro-organisms [35]. Plants' roots secrete reducing molecules [36,37] that can also be utilized for electrical current production in BECs [38]. Rather than direct electricity production, the degradation of roots in the soil releases organic compounds that can be used to feed bacteria in soil MFCs [39].…”
Section: Introductionmentioning
confidence: 99%